Kebudayaan Towani Tolotang Kabupaten Sidenreng Rappang - Muh. Ardiansyah (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2021)
This paper aims to describe the scope of Towani Tolotang culture by explaining the history of the Towani Tolotang people, the spread of Towani Tolotang in Sidenreng Rappang Regency, how Towani Tolotang religiousization in Indonesia, belief systems and social dynamics of the Towani Tolotang people. The method used in this research is descriptive qualitative method, qualitative method is used to describe how the scope of Towani Tolotang culture is located in Sidenrang Rappang Regency. The end of this study will show the cultural implications of the Towani Tolotang community on the local belief system of the community. Keywords: kebudayaan, Towani, Tolotang.